Main barriers to services linked to voluntary pregnancy termination on three grounds in Chile - Montero, Adela; Ramirez-Pereira, Mirliana; Robledo, Paz; Casas, Lidia; Vivaldi, Lieta; González, Daniela (Frontiers in Public Health, 2023)
Introduction After decades of absolute criminalization, on September 14, 2017, Chile decriminalized voluntary termination of pregnancy (VTP) when there is a life risk to the pregnant woman, lethal incompatibility of the embryo or fetus of genetic or chromosomal nature, and pregnancy due to rape. The implementation of the law reveals multiple barriers hindering access to the services provided by the law. Objectives To identify and analyze, using the Tanahashi Model, the main barriers to the implementation of law 21,030 in public health institutions. This article contributes to the follow-up of this public policy, making visible the obstacles that violate women's rights of women to have dignified access to abortion and that affect the quality of health care in Chile. Material and method Qualitative design, following the postpositivist paradigm. The sample consisted of relevant actors directly related to pregnancy termination. Snowball sampling and semi-structured interviews were used. Grounded theory was used through inductive coding, originating categories regrouped into meta-categories following Tanahashi's model. The rigor criteria of transferability, dependability, credibility, authenticity, and epistemological theoretical adequacy were used. The identity of the participants and the confidentiality of the information were protected. Results From January 2021 to October 2022, 62 interviews were conducted with 20 members of the psychosocial support team; 18 managers; 17 members of the biomedical health team; 4 participants from of civil society, and three women users. The main obstacles correspond to availability barriers, accessibility barriers, acceptability barriers, contact barriers, and effectiveness barriers. Conclusions Barriers to access abortion under three grounds violate the exercise of women's sexual and reproductive rights. It is urgent to carry out actions of control and follow-up of this public policy to the corresponding entities.